Tempered glass and preparation method thereof

By optimizing the glass compound material and process parameters, combined with physical tempering and chemical tempering treatment, the problems of insufficient mechanical strength and low production efficiency in the existing glass tempering methods are solved, and efficient tempered glass preparation is achieved.

CN117105525BActive Publication Date: 2024-12-20QINGYUAN CSG NEW ENERGY SAVING MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311079298.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2024-12-20
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

In the existing fiberglass tempering methods, physical tempering has little impact on mechanical strength, and chemical tempering treatment time is long, resulting in low production efficiency.

Method used

By providing a compound material including SiO2, Al2O3, Na2O, K2O and MgO, after melting and forming, physical tempering is carried out, including insulation at a temperature below the softening point temperature for 15 minutes to 30 minutes, and chemical tempering is carried out, and Processing, optimize physical tempering coefficients and process parameters to improve mechanical strength and production efficiency.

Benefits of technology

It improves the strengthening effect of physical tempering treatment, shortens the chemical tempering treatment time, significantly improves the stress layer depth and mechanical properties of tempered glass, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a tempered glass and a preparation method thereof. The preparation method of the tempered glass comprises the following steps: providing a batch material containing SiO2, Al2O3, Na2O, K2O and MgO; the mass fractions of SiO2, Al2O3, Na2O, K2O and MgO in the batch material are respectively a%, b%, c%, d% and e%, satisfying: (a+1.2b+0.8e) / (0.55c+0.45d)=7.85~8.82; melting and molding the batch material to obtain a molded glass; physically tempering the molded glass, which comprises the following steps: subjecting the molded glass to a temperature T B Keep warm for 15min~30min, temperature T B The softening point temperature is 15℃~30℃ lower than that of the molded glass; chemical tempering is performed to obtain tempered glass. This method can give full play to the strengthening effect of physical tempering, shorten the time of chemical tempering, and improve production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, and in particular to tempered glass and a preparation method thereof. Background Art

[0002] With the rapid development of China's economy, the demand for glass in various industries has increased dramatically, such as door and window glass in the construction industry, window glass and windshield glass in vehicles, cover glass of electronic touch devices, etc. After these glasses are processed and formed, they are usually tempered to form a compressive stress layer on the surface of the glass, thereby enhancing the mechanical strength, thermal stability and safety of glass products.

[0003] Glass tempering methods can be divided into physical tempering and chemical tempering, and at least one of these methods can be selected to temper the glass according to the performance requirements of the glass product. However, physical tempering has little effect on the mechanical strength of the glass product, while chemical tempering requires a long processing time, resulting in low production efficiency of tempered glass. Summary of the invention

[0004] Based on this, it is necessary to provide a tempered glass and a preparation method thereof to solve the problem that physical tempering has little effect on the mechanical strength of tempered glass, and chemical tempering requires a long processing time, resulting in low production efficiency.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing tempered glass, comprising the following steps:

[0007] Providing a batch material containing SiO2, Al2O3, Na2O, K2O and MgO; the mass fractions of the SiO2, the Al2O3, the Na2O, the K2O and the MgO in the batch material are respectively a%, b%, c%, d% and e%, satisfying: (a+1.2b+0.8e) / (0.55c+0.45d)=7.85~8.82;

[0008] The batch material is melted and molded to obtain molded glass;

[0009] The shaped glass is subjected to physical tempering treatment; the physical tempering treatment comprises the following steps: subjecting the shaped glass to a temperature T B Keep warm for 15min~30min, the temperature T B 15°C to 30°C lower than the softening point temperature of the molded glass;

[0010] The shaped glass after physical tempering treatment is subjected to chemical tempering treatment to obtain tempered glass.

[0011] In one embodiment, the batch material includes the following components in mass fractions:

[0012] SiO250%~70%;

[0013] Al2O35%~20%;

[0014] Na2O10%~16%;

[0015] K2O4%~8%;

[0016] MgO3%~9%.

[0017] In one of the embodiments, the batch material further includes ZrO2 with a mass fraction of 0.2% to 2%.

[0018] In one embodiment, the physical tempering process comprises the following steps:

[0019] The formed glass is placed in a hot bending mold and gradually heated to the temperature T B ;

[0020] At temperature T B Keep warm for 15min~30min, and perform hot pressing treatment;

[0021] From the temperature T B Gradually cool down to room temperature.

[0022] In one embodiment, the hot pressing treatment comprises the following steps:

[0023] Apply a pressure of 70MPa to 120MPa to the hot bending mold, and maintain the pressure for 10min to 15min.

[0024] In one embodiment, the gradient heating comprises the following steps:

[0025] The temperature is raised from room temperature to 500°C, and the heating time is 35min~45min;

[0026] The temperature rises from 500°C to 700°C, and the heating time is 25min~35min;

[0027] From 700°C to the temperature T B The heating time is 15min~25min.

[0028] In one embodiment, the gradient cooling comprises the following steps:

[0029] From the temperature T B Cool down to 700℃, the cooling time is 15min~25min;

[0030] Cool down from 700℃ to 500℃, the cooling time is 25min~35min;

[0031] The cooling time from 500℃ to room temperature is 35min~45min.

[0032] In one embodiment, the chemical toughening comprises the following steps:

[0033] At a temperature of 400°C to 500°C, the physically tempered shaped glass is subjected to an ion exchange treatment using molten salt for 4h to 6h.

[0034] In one embodiment, the melting process comprises the following steps:

[0035] The batch material is heated to 1600° C. to 1650° C. and kept at this temperature for 5 h to 7 h;

[0036] Cool down to 1550℃~1580℃, keep warm for 0.5h~2h to obtain molten glass.

[0037] In one embodiment, the molding process comprises the following steps:

[0038] The molten glass liquid is poured into a forming mold, and after the molten glass liquid is hardened, it is annealed at 700° C. to 730° C. for 2 h to 4 h.

[0039] A second aspect of the present invention provides a tempered glass, which is prepared by the above-mentioned method for preparing tempered glass.

[0040] In one embodiment, the tempered glass meets one or more of the following conditions:

[0041] (1) The depth of the stress layer is ≥46 μm;

[0042] (2) The stress value is ≥800MPa.

[0043] The present invention has the following beneficial effects:

[0044] The formula (a+1.2b+0.8e) / (0.55c+0.45d)=7.85~8.82 proposed by the present invention enables accurate quantification of the influence of the content of each component in the batch on the physical tempering treatment. By controlling the content of each component, the softening point temperature, softening speed and deformation degree of the glass after physical tempering can be adjusted, thereby improving the strengthening effect of the physical tempering treatment. BKeeping the glass warm for 15 to 30 minutes can improve the matching between the content of each component in the batch and the process parameters of physical tempering, so as to give full play to the strengthening effect of physical tempering on glass and greatly increase the stress layer depth of tempered glass under the condition of minimizing the attenuation of stress value. In addition, the improvement of the effect of physical tempering is conducive to shortening the time required for chemical tempering and improving the production efficiency of tempered glass. DETAILED DESCRIPTION

[0045] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0046] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0048] Physical tempering is a method of heating the glass at a certain heating rate to below the softening point, and then cooling it to form a compressive stress layer on the glass surface, also known as thermal tempering. Chemical tempering is a method of immersing the glass in molten salt, and based on the diffusion of alkali metal ions, causing ion exchange between the molten salt and the glass surface to change the composition of the glass surface and form a compressive stress layer.

[0049] Whether it is flat glass or curved glass, after cutting and CNC processing, it is also necessary to use at least one of physical tempering and chemical tempering to temper the glass product to increase the mechanical strength and thermal stability of the glass product. For example, the processing of curved glass usually includes two processes: thermal bending and chemical tempering. Among them, thermal bending is to heat the glass to a temperature near the softening point and then make the glass thermally bent. Therefore, thermal bending can actually play the role of physical tempering, that is, curved glass can be regarded as a type of tempered glass that has been physically and chemically tempered.

[0050] However, for this type of physically and chemically tempered glass products, their mechanical strength basically depends only on the strengthening effect of chemical tempering, and the improvement of mechanical strength by physical tempering is very small. For example, the hot bending process only deforms the glass without changing its mechanical properties. In addition, since physical tempering does not fully exert its strengthening effect, chemical tempering requires a long processing time to obtain the ideal tempering effect, resulting in low production efficiency.

[0051] After further research, the inventors found that the content of each component of the glass product and the process parameters of physical tempering will affect the effect of physical tempering. In the traditional method, there is no synergy between the content of each component of the glass product and the process parameters of physical tempering. This mismatch results in little effect of physical tempering on the mechanical strength of the glass product.

[0052] Based on this, the first aspect of the present invention provides a method for preparing tempered glass to overcome the problem that physical tempering has little effect on the mechanical strength of tempered glass, and chemical tempering takes a long time to process, resulting in low production efficiency.

[0053] In some embodiments, the method for preparing tempered glass comprises the following steps:

[0054] S1: Provide a batch material containing SiO2, Al2O3, Na2O, K2O and MgO; the mass fractions of SiO2, Al2O3, Na2O, K2O and MgO in the batch material are denoted as a%, b%, c%, d% and e% respectively, the physical tempering coefficient of the formed glass is θ, and the physical tempering coefficient θ satisfies formula (1):

[0055] θ=(a+1.2b+0.8e) / (0.55c+0.45d)=7.85~8.82(1)

[0056] S2: melting and molding the batch materials to obtain molded glass;

[0057] S3: Physically tempering the shaped glass; the physical tempering treatment includes the following steps: subjecting the shaped glass to a temperature TB Keep warm for 15min~30min, and the temperature is T B 15℃~30℃ lower than the softening point of molded glass;

[0058] S4: chemically tempering the formed glass after the physical tempering treatment to obtain tempered glass.

[0059] Among the batch materials, silicon dioxide (SiO2) is the main component of the glass skeleton, which improves the mechanical strength and other properties of the glass, but increases the viscosity of the glass and reduces the corrosion resistance of the glass to etching liquid; aluminum oxide (Al2O3) can improve the strength of the glass and its adaptability to thermal bending deformation, and can greatly increase the ion exchange capacity of the glass, but it will increase the viscosity of the glass and increase the difficulty of clarification; sodium oxide (Na2O) is an essential component for ion exchange and can significantly improve the meltability of the glass; potassium oxide (K2O) can improve the meltability of the glass and increase the depth of stress layers (DOL) after tempering the glass, and can work together with sodium oxide to produce a "mixed alkali effect" to improve the comprehensive performance of the glass; magnesium oxide (MgO) can reduce the viscosity of the glass at high temperatures, promote the melting and clarification of the glass, and increase the stress of the glass after tempering (also known as surface compressive stress, CS).

[0060] According to the influence of the content of each component in the batch on the strength, processability, solubility and ion exchange capacity of the glass, the calculation formula of the physical tempering coefficient θ is fitted, and the physical tempering coefficient θ is limited to the range of 7.85 to 8.82. If the physical tempering coefficient θ is lower than 7.85, the physical tempering treatment will cause the CS value of the tempered glass to attenuate too much; if the physical tempering coefficient θ is higher than 8.82, the physical tempering treatment will greatly reduce the effect of improving the DOL value of the tempered glass.

[0061] Therefore, the physical tempering coefficient θ proposed in the present invention enables the influence of the content of each component in the batch material on the physical tempering treatment to be accurately quantified. By controlling the content of each component to change the physical tempering coefficient θ, the softening point temperature, softening speed and deformation degree of the glass after physical tempering can be adjusted, thereby improving the strengthening effect of the physical tempering treatment. B Keeping the glass warm for 15 to 30 minutes can improve the matching between the content of each component in the batch and the process parameters of physical tempering, so as to give full play to the strengthening effect of physical tempering on glass and greatly improve the DOL value of tempered glass under the condition of minimizing the attenuation of CS value. In addition, the improvement of the effect of physical tempering treatment is conducive to shortening the time required for chemical tempering treatment and improving the production efficiency of tempered glass.

[0062] In some specific examples, the physical toughening coefficient θ can be 7.85, 7.90, 7.95, 8.00, 8.05, 8.10, 8.15, 8.20, 8.25, 8.30, 8.35, 8.40, 8.45, 8.50, 8.55, 8.60, 8.65, 8.70, 8.75, 8.80 or 8.82, etc.

[0063] In some specific examples, the temperature T B The difference from the softening point temperature of the molded glass may be 10°C, 12°C, 14°C, 16°C, 18°C, 20°C, 22°C, 24°C, 26°C, 28°C or 30°C, etc.

[0064] In some embodiments, the batch material includes the following components in mass fractions:

[0065] SiO250%~70%;

[0066] Al2O35%~20%;

[0067] Na2O10%~16%;

[0068] K2O4%~8%;

[0069] MgO3%~9%.

[0070] If the content of SiO2 is less than 50%, the glass forming performance is poor and the hot bending performance is deteriorated; if the content of SiO2 exceeds 70%, the batch material will become refractory and the tendency of crystallization will increase. If the content of Al2O3 is less than 5%, the hot bending performance and ion exchange capacity of the glass are insufficient; if the content of Al2O3 is higher than 20%, the viscosity of the glass is too high and it is difficult to clarify, the melting quality is reduced, which will significantly affect the various properties of the glass and reduce the tempering effect of the hot bending process. If the content of Na2O is less than 10%, the meltability of the glass is poor; if the content of Na2O is higher than 16%, the hot bending performance of the glass deteriorates. If the content of K2O is less than 4%, the meltability of the glass is poor, and it is difficult to achieve the ideal DOL value after strengthening; if the content of K2O is higher than 8%, the weather resistance of the glass deteriorates, and the hot bending performance of the glass is poor. If the content of MgO is less than 3%, the meltability of the glass deteriorates, and it is difficult to achieve the ideal CS value after strengthening. If the MgO content is higher than 9%, the glass will easily crystallize, and the material will be too short and difficult to shape.

[0071] Optionally, the batch material includes the following components in mass fractions:

[0072] SiO255%~65%;

[0073] Al2O310%~18%;

[0074] Na2O12%~15%;

[0075] K2O5%~7%;

[0076] MgO4%~8%.

[0077] Further optionally, the batch material includes the following components in mass fractions:

[0078] SiO258%~64%;

[0079] Al2O311%~15%;

[0080] Na2O12.5%~14.5%;

[0081] K2O5.1%~6%;

[0082] MgO4.2%~6.2%.

[0083] In some embodiments, the batch material further includes ZrO2 with a mass fraction of 0.2% to 2%.

[0084] Adding zirconium oxide (ZrO2) to the batch can improve the weather resistance of tempered glass. If the ZrO2 content is lower than 0.2%, the weather resistance of the glass is insufficient; if the ZrO2 content is higher than 2%, the solubility of the glass deteriorates.

[0085] Optionally, the mass fraction of ZrO2 in the batch is 0.4%~1.5%.

[0086] Further optionally, the mass fraction of ZrO2 in the batch is 0.4%~1.1%.

[0087] Alternatively, let the content of ZrO2 in the batch be f%, then the physical toughening coefficient θ satisfies formula (2): θ=(a+1.2b+0.8e+1.2f) / (0.55c+0.45d+0.15f)=7.85~8.82 (2)

[0088] Since the content of ZrO2 in the batch is ≤2%, the effect on the physical tempering effect is small, so the content of ZrO2 is not included in formula (1). In some specific examples, the physical tempering coefficient θ can also be calculated by formula (2) including the content of ZrO2 to improve the accuracy of the physical tempering coefficient θ.

[0089] In some embodiments, the melt processing includes the following steps:

[0090] Heat the batch material to 1600℃~1650℃ and keep it warm for 5h~7h;

[0091] Cool down to 1550℃~1580℃, keep warm for 0.5h~2h to obtain molten glass.

[0092] In some specific examples, the temperature of the batch material being heated can be 1600°C, 1605°C, 1610°C, 1615°C, 1620°C, 1625°C, 1630°C, 1635°C, 1640°C, 1645°C or 1650°C, etc.; the holding time at a temperature of 1600°C-1650°C can be 5h, 5.5h, 6h, 6.5h or 7h, etc.; the temperature of the batch material after cooling can be 1550°C, 1555°C, 1560°C, 1565°C, 1570°C, 1575°C or 1580°C, etc.; the holding time at a temperature of 1550°C-1580°C can be 0.5h, 1h, 1.5h or 2h, etc.

[0093] In some embodiments, the molding process includes the following steps:

[0094] The molten glass is poured into a molding mold, and after the molten glass is hardened, it is annealed at 700°C~730°C for 2h~4h.

[0095] In some specific examples, the annealing temperature may be 700°C, 705°C, 710°C, 715°C, 720°C, 725°C or 730°C, etc., and the annealing time may be 2h, 2.5h, 3h, 3.5h or 4h, etc.

[0096] Optionally, the molding die includes a graphite molding die and a ceramic molding die.

[0097] Optionally, the forming mold is a rectangular forming mold, and its size may be 200 mm×120 mm (L×W).

[0098] Optionally, before the step of pouring the molten glass into the molding mold, the step of preheating the molding mold to 480°C~500°C is also included. In some specific examples, the preheating temperature of the molding mold can be 480°C, 485°C, 490°C, 495°C or 500°C, etc.

[0099] Optionally, after the molding process, the steps of cutting, grinding, polishing and CNC machining are also included.

[0100] Optionally, the physical tempering treatment includes the following steps: gradually heating the molded glass to a temperature T B ; At temperature T B Keep warm for 15min~30min; from temperature T B Gradually cool down to room temperature.

[0101] Optionally, the physical tempering treatment includes the following steps: placing the formed glass in a hot bending mold, gradually heating it to a temperature TB ; At temperature T B Keep warm for 15min~30min, and perform hot pressing treatment; from temperature T B Gradually cool down to room temperature.

[0102] In the physical tempering process, if the hot bending mold and hot pressing treatment are not used, the obtained tempered glass is flat glass; if the hot bending mold and hot pressing treatment are used, the obtained tempered glass is curved glass. That is, the preparation method of tempered glass provided by the present invention is applicable to the tempering of flat glass and curved glass.

[0103] Through gradient heating and cooling treatments, the molded glass can be deformed slowly and safely, avoiding defects such as warping, deformation, and cracking caused by drastic temperature changes. It is also beneficial to eliminate the thermal stress generated during the physical tempering process and improve the mechanical properties and thermal stability of tempered glass.

[0104] Optionally, the hot bending mold includes a graphite hot bending mold and a ceramic hot bending mold.

[0105] Optionally, the hot pressing treatment comprises the following steps:

[0106] Apply a pressure of 70MPa to 120MPa to the hot bending mold, and maintain the pressure for 10min to 15min.

[0107] Optionally, the gradient heating comprises the following steps:

[0108] The temperature is raised from room temperature to 500°C, and the heating time is 35min~45min;

[0109] The temperature rises from 500°C to 700°C, and the heating time is 25min~35min;

[0110] From 700℃ to temperature T B The heating time is 15min~25min.

[0111] Optionally, the gradient cooling comprises the following steps:

[0112] From the temperature T B Cool down to 700℃, the cooling time is 15min~25min;

[0113] Cool down from 700℃ to 500℃, the cooling time is 25min~35min;

[0114] The cooling time from 500℃ to room temperature is 35min~45min.

[0115] In some embodiments, chemical toughening comprises the following steps:

[0116] At a temperature of 400°C to 500°C, the physically tempered shaped glass is subjected to an ion exchange treatment using molten salt for 4h to 6h.

[0117] In some specific examples, the temperature of chemical tempering can be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C or 500°C, etc.; the time of ion exchange treatment can be 4h, 4.5h, 5h, 5.5h or 6h, etc.

[0118] Optionally, the molten salt includes hydrochloride molten salt and / or nitrate molten salt.

[0119] Optionally, the cations in the molten salt include lithium ions (Li + ), sodium ion (Na + ), potassium ion (K + ), rubidium ions (Rb + ), cesium ion (Cs + ) and francium ions (Fr + )

[0120] Further optionally, the molten salt is potassium nitrate molten salt.

[0121] A second aspect of the present invention provides a tempered glass, which is prepared by the above-mentioned method for preparing tempered glass.

[0122] Optionally, the stress layer depth of the tempered glass is ≥46μm. In some specific examples, the stress layer depth of the tempered glass may be 46μm, 47μm, 48μm, 49μm, 50μm, 51μm, 52μm, 53μm, 54μm, 55μm or 60μm, etc.

[0123] Optionally, the stress value of the tempered glass is ≥800 MPa. In some specific examples, the stress value of the tempered glass can be 800 MPa, 810 MPa, 820 MPa, 830 MPa, 840 MPa, 850 MPa, 860 MPa, 870 MPa, 880 MPa, 890 MPa, 900 MPa, 910 MPa, 920 MPa or 950 MPa, etc.

[0124] Taking the tempered glass that has only undergone the same chemical tempering treatment as a benchmark, the CS value increment (∆CS) of the tempered glass of the present invention is ≥-81MPa, the DOL value increment (∆DOL) is ≥6.3μm, the attenuation amplitude of the CS value is small and the increase amplitude of the DOL value is large, the physical tempering effect is significant, and the mechanical strength performance is excellent.

[0125] Physical tempering temperature T B Only 15℃~30℃ lower than the softening point of molded glass, at temperature TB After 15-30 minutes of heat preservation, the internal structure of the glass will become loose. On the one hand, this will partially offset the "crowding effect" caused by chemical tempering, resulting in a decrease in the CS value, that is, a negative ∆CS value; on the other hand, this loose structure is conducive to the K in the molten salt during chemical tempering. + And Na deeper inside the glass + Ion exchange occurs, which increases the DOL value, that is, ∆DOL is a positive value. The performance of glass is determined by both the CS value and the DOL value, and the increase in the DOL value is sufficient to compensate for the negative impact of the decrease in the CS value.

[0126] The increment of DOL value can be estimated by using formula (3), and its error is about ±2.5μm. In formula (3), t is the temperature T B The insulation time below.

[0127] (3)

[0128] The present invention is further described in detail below in conjunction with specific examples. In the following specific examples and comparative examples, the raw materials used, unless otherwise specified, are all commercially available products; the instruments used, unless otherwise specified, are all commercially available products; the processes used, unless otherwise specified, are all conventionally selected by those skilled in the art.

[0129] Example 1

[0130] (1) Ingredients: Please refer to Table 1. Based on 1400 g of molten glass, weigh SiO2, Al2O3, Na2O, K2O, MgO and ZrO2, grind them and mix them evenly to obtain a batch material.

[0131] (2) Melting: Place the batch materials in a platinum crucible, and place the platinum crucible in a lifting furnace. Heat to 1600℃~1650℃, keep warm for 6 hours, then reduce the temperature to 1550℃~1580℃, and keep warm for another hour to obtain molten glass.

[0132] (3) Molding: Preheat a rectangular graphite molding mold with a size of 200 mm × 120 mm (L × W) to 480 ° C ~ 500 ° C, and pour the molten glass into the rectangular graphite molding mold. After the rectangular graphite molding mold is hardened, transfer it to an annealing furnace that has been heated to 700 ° C ~ 730 ° C, keep it warm for 3 hours, and take it out after cooling to room temperature with the furnace; cut the annealed glass into thin sheets of 155 mm × 80 mm × 1.1 mm (L × W × H), double-sided grinding and polishing, and CNC processing are performed to obtain molded glass.

[0133] (4) Physical tempering: Place the formed glass in a graphite hot bending mold, and then place the graphite hot bending mold in a physical tempering furnace and gradually heat it to temperature T B ; At temperature T B Keep the temperature for t min, and perform hot pressing, then B Gradually cool down to room temperature.

[0134] Among them, the softening point temperature of the molded glass is T S is 770℃, the physical toughening coefficient θ is 8.02, and the temperature T B The temperature is 750℃ and the holding time t is 30min.

[0135] The gradient heating program is as follows: from room temperature to 500 °C, the heating time is 40 min; from 500 °C to 700 °C, the heating time is 30 min; from 700 °C to temperature T B , the heating time is 20min.

[0136] The hot pressing treatment procedure is: apply a pressure of 70MPa~120MPa to the hot bending mold and maintain the pressure for 10min~15min.

[0137] The gradient cooling program is: from temperature T B The temperature is lowered to 700°C in 20 minutes; from 700°C to 500°C in 30 minutes; from 500°C to room temperature in 40 minutes.

[0138] (5) Chemical tempering: The physically tempered shaped glass is placed in a potassium nitrate molten salt at 420°C for 5 hours for ion exchange treatment to obtain tempered glass.

[0139] Example 2

[0140] The preparation method of this embodiment is basically the same as that of embodiment 1, except that: the physical toughening coefficient θ is 7.85, the softening point temperature T S is 775℃, temperature T B The temperature is 750℃ and the holding time t is 25min.

[0141] Example 3

[0142] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 8.36, the softening point temperature T S is 792℃, temperature T B The temperature is 765℃ and the holding time t is 25min.

[0143] Example 4

[0144] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 8.58, the softening point temperature T S is 756℃, temperature T B The temperature is 740℃ and the holding time t is 30min.

[0145] Example 5

[0146] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 8.67, the softening point temperature T S is 787℃, temperature T B The temperature is 770℃ and the holding time t is 15min.

[0147] Example 6

[0148] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 8.29, the softening point temperature T S is 764℃, temperature T B The temperature is 745℃ and the holding time t is 30min.

[0149] Example 7

[0150] The preparation method of this embodiment is basically the same as that of embodiment 1, except that: the physical toughening coefficient θ is 8.80, the softening point temperature T S is 783℃, temperature T B The temperature is 760℃ and the holding time t is 15min.

[0151] Example 8

[0152] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 8.82, the softening point temperature T S is 800℃, temperature T B The temperature is 780℃ and the holding time t is 15min.

[0153] Example 9

[0154] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 8.05, the softening point temperature T S is 780℃, temperature T B The temperature is 760℃ and the holding time t is 20min.

[0155] Example 10

[0156] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 8.15, the softening point temperature T S is 768℃, temperature T B The temperature is 750℃ and the holding time t is 20min.

[0157] Embodiment 11

[0158] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 7.90, the softening point temperature T S is 769℃, temperature T B The temperature is 750℃ and the holding time t is 25min.

[0159] Example 12

[0160] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the physical toughening coefficient θ is 7.90, the softening point temperature T S is 759℃, temperature T B The temperature is 740℃ and the holding time t is 30min.

[0161] Comparative Examples 1 to 3

[0162] The preparation method of this comparative example is basically the same as that of Example 1, except that the physical toughening coefficient θ is lower than 7.85.

[0163] Comparative Example 4

[0164] The preparation method of this comparative example is basically the same as that of Example 1, except that the physical toughening coefficient θ is higher than 8.82.

[0165] Comparative Example 5

[0166] The preparation method of this comparative example is basically the same as that of Example 5, except that: the temperature T B and softening point temperature T S The difference exceeds 30°C.

[0167] Comparative Example 6

[0168] The preparation method of this comparative example is basically the same as that of Example 9, except that: B The holding time is less than 15min.

[0169] Comparative Example 7

[0170] The preparation method of this comparative example is basically the same as that of Example 5, except that: the temperature T Band softening point temperature T S The difference is less than 15°C.

[0171] Comparative Example 8

[0172] The preparation method of this comparative example is basically the same as that of Example 9, except that: B The holding time is higher than 30min.

[0173] Test Case

[0174] According to the formula in Table 1, the physical toughening coefficient θ is calculated according to formula (1), and the results are shown in Table 2. The viscosity of the molten glass obtained by melting is tested using a RSV-1600 high-temperature rotational viscometer, and the softening point temperature T of the molded glass is obtained after fitting. S , the results are shown in Table 2.

[0175] For the same embodiment or the same comparative example, the tempered glass that has been subjected to physical tempering treatment and chemical tempering treatment is recorded as sample A, and the tempered glass that has not been subjected to physical tempering treatment but has only been subjected to chemical tempering treatment is recorded as sample B. The CS value and DOL value of sample A and sample B are respectively measured using a FSM-6000LE stress meter and are recorded as CS and DOL, respectively. A , CS B 、DOL A and DOL B , and calculate ∆CS (∆CS=CS A -CS B ) and ∆DOL (∆DOL = DOL A -DOL B ), the results are shown in Table 2. The photoelastic coefficient used in the test is 27.5nm / (cm·MPa) and the refractive index is 1.51.

[0176] It can be seen from Table 2 that the physical toughening coefficients θ of Examples 1 to 12 are all controlled within the range of 7.85 to 8.82, and the softening point temperature T S With temperature T B The difference ∆T (∆T = T S -T B ) are controlled within the range of 15℃~30℃, at temperature T B The holding time t is controlled within the range of 15min~30min. After physical and chemical tempering, CS A The value is 839MPa~874MPa, DOL AThe value is 46.2μm~50.1μm; compared with sample B that has only been chemically tempered, the ∆CS value is ≥-81MPa, and the ∆DOL value is at least 6.3μm, indicating that physical tempering treatment can significantly improve the mechanical properties of tempered glass and thus shorten the processing time of chemical tempering.

[0177] The physical toughening coefficient θ of Comparative Examples 1 to 3 is lower than 7.85; the ∆CS values ​​of Comparative Examples 1 to 2 are comparable to those of Examples 1 to 12, but the ∆DOL values ​​are only 3.2 μm and 4.4 μm, and the increase in the depth of the stress layer is relatively low; the ∆DOL value of Comparative Example 3 reaches 8.4 μm, but the ∆CS value is -117 MPa, and the stress attenuation amplitude is too large.

[0178] The physical toughening coefficient θ of Comparative Example 4 is higher than 8.82, and its ∆CS value is comparable to that of Examples 1 to 12, but its ∆DOL value is only 3.1 μm, and the increase in the depth of the stress layer is relatively low.

[0179] The temperature of comparative example 5 is 67°C lower than the softening point temperature, and the insulation time of comparative example 6 is only 5 minutes. The ∆CS values ​​of the two are reduced compared with embodiments 1 to 12, and the ∆DOL values ​​are only 3.6μm and 2.2μm, and the increase in the depth of the stress layer is relatively low.

[0180] The temperature of Comparative Example 7 is only 7°C lower than the softening point temperature, and the insulation time of Comparative Example 8 reaches 40 min. The ∆DOL values ​​of the two are slightly higher than those of Examples 1 to 12, but the ∆CS values ​​reach -125 MPa and -108 MPa, and the stress value attenuation range is too large.

[0181] It can be seen that the physical toughening coefficient θ and temperature T B Only by controlling the three parameters of temperature, holding time t at the same time can the strengthening effect of physical tempering be fully exerted, thereby greatly improving the DOL value of tempered glass while minimizing the attenuation of CS value.

[0182] Table 1. Content of each component in the batch (wt.%)

[0183]

[0184] Table 2. Process parameters and mechanical properties of tempered glass

[0185]

[0186] For the glass of the present invention, the technical features of the above-mentioned embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0187] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A method for preparing tempered glass, characterized in that: The following steps are involved: Providing a batch material containing SiO2, Al2O3, Na2O, K2O and MgO; The batch material includes the following components by mass fraction: SiO2 50%~70%; Al2O3 5%~20%; Na2O 10%~16%; K2O 4%~8%; MgO 3%~9%; The mass fractions of SiO2, Al2O3, Na2O, K2O and MgO in the batch are respectively a%, b%, c%, d% and e%, satisfying: (a+1.2b+0.8e) / (0.55c+0.45d)=7.85~8.82; The batch material is melted and molded to obtain molded glass; The shaped glass is subjected to physical tempering treatment; the physical tempering treatment comprises the following steps: subjecting the shaped glass to a temperature T B Keep warm for 15min~30min, the temperature T B 15°C to 30°C lower than the softening point temperature of the molded glass; Performing chemical tempering treatment on the shaped glass after physical tempering treatment to obtain tempered glass; Taking the tempered glass that has not been subjected to the physical tempering treatment but has only been subjected to the chemical tempering treatment as a benchmark, the increment of the CS value of the tempered glass that has been subjected to the physical tempering treatment and the chemical tempering treatment is ≥-81MPa, and the increment of the DOL value is ≥6.3μm.

2. The method for preparing tempered glass according to claim 1, characterized in that: The batch material includes the following components by mass fraction: SiO2 55%~65%; Al2O3 10%~18%; Na2O 12%~15%; K2O 5%~7%; MgO 4%~8%.

3. The method for preparing tempered glass according to claim 2, characterized in that: The batch material also includes ZrO2 with a mass fraction of 0.2% to 2%.

4. The method for preparing tempered glass according to any one of claims 1 to 3, characterized in that: The physical toughening treatment comprises the following steps: The formed glass is placed in a hot bending mold and the temperature is gradually increased to the temperature T B ; At temperature T B Keep warm for 15min~30min, and perform hot pressing treatment; From the temperature T B Gradually cool down to room temperature.

5. The method for preparing tempered glass according to claim 4, characterized in that: The hot pressing treatment comprises the following steps: Apply a pressure of 70MPa to 120MPa to the hot bending mold, and maintain the pressure for 10min to 15min.

6. The method for preparing tempered glass according to claim 4, characterized in that: The gradient heating comprises the following steps: The temperature is raised from room temperature to 500°C, and the heating time is 35min~45min; The temperature rises from 500°C to 700°C, and the heating time is 25min~35min; From 700°C to the temperature T B The heating time is 15min~25min.

7. The method for preparing tempered glass according to claim 4, characterized in that: The gradient cooling comprises the following steps: From the temperature T B Cool down to 700℃, the cooling time is 15min~25min; Cool down from 700℃ to 500℃, the cooling time is 25min~35min; The cooling time from 500℃ to room temperature is 35min~45min.

8. The method for preparing tempered glass according to any one of claims 1 to 3, characterized in that: The chemical toughening comprises the following steps: At a temperature of 400°C to 500°C, the physically tempered shaped glass is subjected to an ion exchange treatment using molten salt for 4h to 6h.

9. The method for preparing tempered glass according to any one of claims 1 to 3, characterized in that: The melting process comprises the following steps: The batch material is heated to 1600° C. to 1650° C. and kept at this temperature for 5 h to 7 h; Cool down to 1550℃~1580℃, keep warm for 0.5h~2h to obtain molten glass.

10. The method for preparing tempered glass according to claim 9, characterized in that: The molding process comprises the following steps: The molten glass liquid is poured into a forming mold, and after the molten glass liquid is hardened, it is annealed at 700° C. to 730° C. for 2 h to 4 h.

11. The method for preparing tempered glass according to any one of claims 1 to 3, characterized in that: The tempered glass meets one or more of the following conditions: (1) The depth of the stress layer is ≥46 μm; (2) The stress value is ≥800MPa.

Citation Information

Patent Citations

  • Tempered screen protector for curved mobile phone and preparation method of tempered screen protector of curved mobile phone

    CN107187139A

  • High-alkali aluminosilicate glass, chemically toughened glass, preparation method and application

    CN115872616A